-3(2s-2)-6=-3(8s+6)-5

Simple and best practice solution for -3(2s-2)-6=-3(8s+6)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2s-2)-6=-3(8s+6)-5 equation:


-3(2s-2)-6=-3(8s+6)-5

We simplify the equation to the form, which is simple to understand
-3(2s-2)-6=-3(8s+6)-5

Reorder the terms in parentheses
+(-6s+6)-6=-3*(8s+6)-5

Remove unnecessary parentheses
-6s+6-6=-3+*(+8s+6+)-5

Reorder the terms in parentheses
-6s+6-6=+(-24s-18)-5

Remove unnecessary parentheses
-6s+6-6=-24s-18-5

We move all terms containing s to the left and all other terms to the right.
-6s+24s=-18-5-6+6

We simplify left and right side of the equation.
+18s=-23

We divide both sides of the equation by 18 to get s.
s=-1.27777777778

See similar equations:

| z-9=12+13 | | 16*-4*p*1=0 | | 3x-9=-7x+11 | | -3(t+5)+10=3(1-t)-2t | | 5(2x-3)=3(3x+6)+x | | 6(1+4a)-6a=-39+3a | | 6(m+2)=15 | | -5-4n=-5(1+5n) | | 5x+8=4x+12 | | 3w=6+6 | | -5-4=-5(1+5n) | | -7+4(7-p)=23-3p | | 2=-2x+22 | | 10y+9.6=(-17.4) | | 3x-7=-31-5x | | p/-5+6=-5 | | 9-3x=-6y | | -x+.5=4 | | .5-x=4 | | y=-3(-8)-15 | | x^2-400x+12500=0 | | 2(a-3)=2 | | (9-3x)/-6 | | 6(x+1)=8x+10 | | 1/4y-4/5+3/2=5/4y-2/3 | | 121/j=11 | | 3(q-2)+2=5q+-7+2q | | x=4+.5 | | .5x=-4 | | x-.5=4 | | 9-3v=-6y | | 338.1/69 |

Equations solver categories